2016
DOI: 10.5194/acp-16-2243-2016
|View full text |Cite
|
Sign up to set email alerts
|

Anvil microphysical signatures associated with lightning-produced NO<sub><i>x</i></sub>

Abstract: Abstract. Thunderstorm anvils were studied during the Deep Convective Clouds and Chemistry experiment (DC3), using in situ measurements and observations of ice particles and NO x together with radar and Lightning Mapping Array measurements. A characteristic ice particle and NO x signature was found in the anvils from three storms, each containing high lightning flash rates in the storm core prior to anvil sampling. This signature exhibits high concentrations of frozen droplets (as measured by a Cloud Droplet P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The laboratory studies of Saunders and Wahab (1975) and Wahab (1974) showed that in a vertical electric field (i.e., the field was aligned with the direction of fall) a threshold of ice crystal concentration of 250/L and an electric field threshold of~60 kV/m was required in order to enhance aggregation. In another study Stith et al (2016) have observed chain-like aggregation of frozen cloud droplets in the upper parts of some anvils in association with high values of NO x in which lightning was known to have occurred. They attributed the aggregation of frozen droplets to electric field forces.…”
Section: Images Of the Particlesmentioning
confidence: 89%
“…The laboratory studies of Saunders and Wahab (1975) and Wahab (1974) showed that in a vertical electric field (i.e., the field was aligned with the direction of fall) a threshold of ice crystal concentration of 250/L and an electric field threshold of~60 kV/m was required in order to enhance aggregation. In another study Stith et al (2016) have observed chain-like aggregation of frozen cloud droplets in the upper parts of some anvils in association with high values of NO x in which lightning was known to have occurred. They attributed the aggregation of frozen droplets to electric field forces.…”
Section: Images Of the Particlesmentioning
confidence: 89%
“…Journal of Geophysical Research: Atmospheres 2.7. Cloud Structure Analyses of cloud physical properties were conducted using aircraft measurements of cloud particle size distributions (Stith et al, 2016) and water vapor (Diao et al, 2017), as well as balloon-borne video disdrometer (Waugh et al, 2018). The recently developed balloon-borne microphysics probe can provide observations at fine scales and give calculated cloud particle mixing ratios and reflectivity in agreement with radar and cloud-resolving, kinematic model results.…”
Section: 1029/2019jd030944mentioning
confidence: 99%
“…The frozen drop aggregates are formed by electrical forces associated with high electric fields accompanying lightning. Since lightning is also the source of lightning-NO x , these studies suggested that electrically active storms may have characteristically different ice particle types in the anvil compared to less electrically active storms, which may have an impact on the radiative impacts of the anvil clouds (Stith et al, 2016).…”
Section: 1029/2019jd030944mentioning
confidence: 99%
“…There is a renewed interest in how lightning characteristics influence NO x and other chemical species, including recent studies emanating from the Deep Convective Cloud and Chemistry (DC3) experiment (e.g., Barth et al, 2015;Carey et al, 2016;DiGangi et al, 2016;Mecikalski et al, 2015;Mecikalski & Carey, 2017;Pollack et al, 2016;Stith et al, 2016). However, as mentioned, only Mecikalski and Carey (2017) separately classified hybrid flashes from CG flashes in their study.…”
Section: Introductionmentioning
confidence: 99%